Brain morphological defects in prolidase deficient mice: first report - V. Insolia; V.M. Piccolini (European Journal of Histochemistry, 2014)
Prolidase gene (PEPD) encodes prolidase enzyme, which is responsible for hydrolysis of dipeptides containing proline or hydroxyproline at their C-terminal end. Mutations in PEPD gene cause, in human, prolidase deficiency (PD), a rare autosomal recessive disorder. PD patients show reduced or absent prolidase activity and a broad spectrum of phenotypic traits including various degrees of mental retardation. This is the first report correlating PD and brain damages using as a model system prolidase deficient mice, the so called dark-like (dal) mutant mice. We focused our attention on dal postnatal brain development, revealing a panel of different morphological defects in the cerebral and cerebellar cortices, such as undulations of the cerebral cortex, cell rarefaction, defects in cerebellar cortex lobulation, and blood vessels overgrowth. These anomalies might be ascribed to altered angiogenic process and loss of pial basement membrane integrity. Further studies will be directed to find a correlation between neuroarchitecture alterations and functional consequences.